KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA SELAMA MASA PANDEMI COVID-19 - Kustinah, Siti (KOMITMEN: Jurnal Ilmiah Manajemen, 2021)
Various types of businesses in Indonesia experienced a decline in their financial performance as a result of the Covid-19 pandemic which had a negative effect on the economy. The purpose of carrying out this research is to be able to see how the effects of the Covid-19 pandemic on the financial performance of several companies listed on the Indonesia Stock Exchange. The research sample used was 214 companies with data analysis using the Wilcoxon Signed-Rank test. The research then succeeded in finding that there was an increase in the leverage ratio and the short-term activity ratio. However, during the pandemic, it was found that there was a decline in the liquidity ratio and profitability ratio. This increase and decrease changed before the pandemic to the current pandemic. KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA SELAMA MASA PANDEMI COVID-19